First two and a half years of aerosol measurements with an AERONET sunphotometer at the Huancayo Observatory, Peru - Estevan, René (2019)
Direct sun measurements with a CIMEL sunphotometer belonging to the AERONET network have been performed in the Huancayo Observatory, Peru, from March 2015 to August 2017, two and a half years, providing for the first time information about aerosols in the specific area. The prevalence of background conditions in the measurement site has been determined for the period of study. These conditions, which constitute more than 80% of cases, are occasionally altered, mainly by high aerosols loading, as a consequence of biomass-burning events. Biomass-burning periods cover every year from mid-July to mid-October. The identification of these periods has been possible through the classification of aerosols in 6 subtypes. The month with the maximum AOD monthly average is September, and in 2016, the absolute maximum value of 0.91 was registered. The mean AOD value for the study period is 0.10 ±0.07 and the alpha mean value is 1.49 ±0.36, indicating presence, of small size aerosols. Some aerosol optical properties were analyzed in order to validate the aerosol classification. The aerosol size distribution revealed a bimodal character with a slight predominance of the fine mode, related to the two main types of aerosols: continental and biomass.